A cost-benefit analysis for reconfigurable PV modules under shading. (15th January 2019) - Baka, M.; Manganiello, P.; Soudris, D.; Catthoor, F.
Highlights: Reconfiguration of solar cells is used to improve energy production of PV modules. Performance of reconfigurable Snake PV modules under shading are examined. Additional cost of reconfigurable Snake PV modules are taken into account. Cost-Energy analysis to compare reconfigurable Snake PV modules to conventional. Profitability of reconfigurable PV modules over 20 years of operation demonstrated. Abstract: Non-uniform conditions within a PV module lead to significant energy losses in conventional topologies. Some of the energy lost due to partial shading can be recovered by installing reconfigurable modules. In order to explore the potential benefits of reconfigurable topologies in installations where non-uniform conditions are dominant, three shading scenarios are simulated throughout the year, both for reconfigurable and conventional modules. This allows the evaluation of the performance of each topology and estimation of the long-term gains. Using a cost function, which includes the additional investment cost, the energy gain can be translated to financial terms. Through this, locations where reconfigurable topologies can be beneficial, both in energy and financial terms, can be identified. The methodology is applied to the case of reconfigurable PV modules with a snake-like configuration. Simulation results show that these PV modules allow for higher energy production compared to conventional modules under all the simulated shading scenarios. However, they remain economically profitable over 20 years only in locations where partial shading is expected to occur daily, either throughout the full year or at least in the period of the year where energy generation is high.